Insomnia in patients with advanced lung cancer admitted to palliative care services. Issue 10 (27th June 2021) - Mercadante, Sebastiano; Valle, Alessandro; Cartoni, Claudio; Pizzuto, Massimo
Abstract: Aim: To assess the prevalence of insomnia and possible associated factors in patients with advanced lung cancer admitted to different settings of palliative care. Methods: Secondary analysis of a consecutive sample of patients with advanced lung cancer receiving palliative care. Epidemiological and clinical data, treatments received in the last month, Karnofsky status, Edmonton Symptom Assessment System (ESAS), Athens Insomnia Scale and the Hospital Anxiety and Depression Scale (HADS), as well as concomitant medical treatment were recorded. Results: One‐hundred‐eight‐two patients with advanced lung cancer were surveyed. The mean age was 69.9 years (SD 10.8), and 121 patients (66%) were men. The majority of patients showed consistent levels of insomnia. A poor Karnofsky level, pain, nausea, and drowsiness, time from diagnosis (1‐3 years), HADS anxiety, and HADS depression, were positively associated with insomnia. Conclusions: About 50% of patients with advanced lung cancer admitted to palliative care services had relevant insomnia. Several factors associated with insomnia have been identified and should prompt physicians for a careful examination and subsequent treatment.